The Challenges of STEAM Instruction: Lessons from the Field. (3rd April 2019) - Herro, Danielle; Quigley, Cassie; Cian, Heidi
ABSTRACT: STEAM (science, technology, engineering, art, and mathematics) education is gaining popularity in schools across the United States and in parts of Europe, Asia, and Australia. Despite its popularity little empirical data exists to guide effective instructional practices, and even less is known about the challenges associated with instruction. Drawing on results of a qualitative longitudinal study, this article presents findings regarding instructional challenges faced by 33 math and science teachers when implementing STEAM units in their classrooms during intensive yearlong professional development. Challenges included pacing/time, student understanding of content and process, issues relating to planning, and concerns about school district policies. Two other challenges that were less frequent, but still notable, included technology integration and issues related to assessment. The article concludes with implications for educational researchers and educators to consider when planning effective STEAM instruction.